Incentive‐Compatible in Dominant Strategies Mechanism Design for an Assembler under Asymmetric Information. Issue 2 (27th August 2018) - Li, Zhaolin; Ryan, Jennifer K.; Shao, Lusheng; Sun, Daewon
Abstract : Assembly systems, in which various components are sourced from multiple suppliers and assembled into the final product, which is sold to external customers, are found in a variety of industries. In many practical settings, the assembler possesses incomplete information regarding the marginal cost of each supplier. This lack of complete information poses a challenge for the assembler in designing contract mechanisms. In this study, we investigate the assembler's contract design problem by proposing a contracting mechanism that can significantly outperform an alternative mechanism that was previously presented in the literature, especially when the uncertainty regarding customer demand is significant. Our mechanism is incentive compatible in dominating strategies (ICDS) and maximizes the assembler's expected profit while ensuring that every supplier truthfully reveals their own production cost, regardless of how the other suppliers might behave. In this ICDS mechanism, the assembler orders the same number of components from each supplier. This 'balanced ordering' property does not hold for the alternative mechanism from the literature. Finally, to simplify the proposed ICDS mechanism, we introduce a hybrid mechanism, under which the complexity of the contract offered to a given supplier depends on the importance of that supplier to the assembler's overall profit. We conduct a set of numerical experiments to demonstrate that, in many cases, this proposed hybrid mechanism provides performance close to that of the optimal mechanism, and can significantly outperform the alternative mechanism from the literature.